DEVELOPING MULTICULTURAL EDUCATION-BASED SOCIAL STUDIES TRAINING MODEL FOR TEACHER’S PROFESSIONAL COMPETENCIES - Musadad, Akhmad Arif (The Journal of Educational Development, 2013)
This study is meant: (1) to describe the existing training models (2) to conduct the need analysis for training models, (3) to design a Multicultural Education-Based Social Studies Training (MEBSS) model, (4) to describe the result of expert and practitioner teams’ evaluation on the training model, (5) to describe the result of participant’s evaluation, and (6) to describe the MEBSS training final model. This research and development was conducted in Surakarta City. The subject of research was Social Studies teachers of Junior High Schools. The qualitative and quantitative data were collected. The results of the research and development show that (1) TOT was a form of training currently used, with a multilayered principle at central, provincial, and regency/city government level; (2) the teachers wanted to improve their competencies through MEBSS training; (3) the MEBSS training model was developed with three stages: planning, implementation and evaluation; (4) the expert team and practitioners rated that the MEBSS training model had met the principles of training management and could be used for the teacher training; (5) participants rated that the MEBSS training model was applicable, and useful for improving the teacher’s competency; and (6) the final form of MEBSS training model contained three stages: the planning stage includes demand analysis, decision establishment, program design, and training kits, the implementation stage includes multiculturalism competency, analysis on KD, syllabus and RPP development, and peer teaching; and training evaluation stage includes follow-up program implementation and implementation of training result in the field.